Hyponatremia is the valuable manifestation for initiating diagnosis of hypopituitarism in elderly - Asano, Tomoko; Sasaki, Masami; Ikoma, Aki; Kakei, Masahumi; Kawakami, Masanobu; Aoki, Atsushi; Ishikawa, San-e (ENDOCRINE JOURNAL, 2012)
The present study was undertaken to determine clinical features of hypopituitarism in elderly subjects. Thirty-one elderly patients with hypopituitarism were enrolled. They were 19 males and 12 females, with the ages of 70.7±5.4 years ranging from 62 to 80 years. High prevalence of hyponatremia (80.6%) and hypoglycemia (29.0%) was found, and it was totally different from that in hypopituitarism from general population. There were two groups of hyponatremia derived from their clinical courses, namely, acute deterioration of hyponatremia and chronically persistent hyponatremia. Analysis for deficient hormones clearly showed that ACTH deficiency was highly found in 30 of 31 patients. There was no difference in serum cortisol levels between the hyponatremic and normonatremic patients. Despite hypoosmolality, plasma arginine vasopressin (AVP) was apparently high in the hyponatremic patients compared with in the normonatremic ones. The present study indicates that hyponatremia is the valuable finding for initiating diagnosis of hypopituitarism, and that augmented release of AVP may be involved in developing hyponatremia in elderly patients with hypopituitarism.